1977
DOI: 10.1111/j.1467-8306.1977.tb01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Impacts on Wisconsin Stream Channels∗

Abstract: The conversion of natural land cover to agricultural land uses in the Platte watershed of southwestern Wisconsin caused a three-to fivefold increase in the magnitudes of floods that recur more frequently than once in five years in the small headwater and tributary watersheds. The impact of settlement on floods is less for larger watersheds, but the general impact of settlement has caused a major channel metamorphosis throughout the Platte River channel system. Most headwater and tributary channels have modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
157
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(160 citation statements)
references
References 1 publication
3
157
0
Order By: Relevance
“…Furthermore, land use changes that alter stream hydrology will impact nutrient retention (Meyer et al, 1999), especially during periods of high biotic activity. Several investigations have shown that alterations in stream hydrology and channel morphology are often associated with a shift in catchment land use from forest to agriculture (Knox, 1977;Jacobson and Primm, 1997). Furthermore, destruction of the riparian zone produces changes in stream morphology and hydrology (Hickin, 1984), along with biological attributes of the system (e.g., see Stauffer et al, 2000), further altering in-stream processes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, land use changes that alter stream hydrology will impact nutrient retention (Meyer et al, 1999), especially during periods of high biotic activity. Several investigations have shown that alterations in stream hydrology and channel morphology are often associated with a shift in catchment land use from forest to agriculture (Knox, 1977;Jacobson and Primm, 1997). Furthermore, destruction of the riparian zone produces changes in stream morphology and hydrology (Hickin, 1984), along with biological attributes of the system (e.g., see Stauffer et al, 2000), further altering in-stream processes.…”
Section: Discussionmentioning
confidence: 99%
“…Stream ecosystems may be influenced by regional variation in climate, watershed hydrology, and terrestrial vegetation (Minshall et al 1983) but because a large majority of data came from temperate to semi-arid watersheds within the continental United States and western Europe, sites were not separated according to geography or climate. Human activities in watersheds can alter stream morphology, increasing or decreasing wetted stream area depending on sediment inputs, hydrology and riparian modification (e.g., Knox 1977). Data analyses presented here were normalized per unit area of stream bottom; inadequate information was available to assess the effects of human alterations of channel morphology on total streambed area.…”
Section: Approach and Data Characteristicsmentioning
confidence: 99%
“…Although the individual processes controlling bank failure in different locales have been well defined (e.g., Lawler 1992Lawler , 1993, our understanding of the basin-wide distribution of bank failure and stability is still in its infancy. Few geographic studies have looked at basin-wide distributions of bank failure per se (Lawler et al 1999), focusing instead on watershed-wide distributions of lateral migration and overall stream cross-sectional changes as a function of disturbances such as agriculture (e.g., Knox 1977), loss of vegetative cover (Graf 1979), climate change (Graf 1987), channelization (Simon 1989), dams (Williams and Wolman 1984), and urbanization (Trimble 1997). Although the changes in channel cross-sections and the controlling processes documented by these and other researchers are related to bank failure, they are not direct measures of that phenomenon.…”
mentioning
confidence: 99%